2011
DOI: 10.1038/npp.2011.284
|View full text |Cite
|
Sign up to set email alerts
|

R7BP Modulates Opiate Analgesia and Tolerance but not Withdrawal

Abstract: The adaptor protein R7 family binding protein (R7BP) modulates G protein coupled receptor (GPCR) signaling and desensitization by controlling the function of regulator of G protein signaling (RGS) proteins. R7BP is expressed throughout the brain and appears to modulate the membrane localization and stability of three proteins that belong to R7 RGS family: RGS6, RGS7, and RGS9-2. RGS9-2 is a potent negative modulator of opiate and psychostimulant addiction and promotes the development of analgesic tolerance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…Mice were anesthetized with avertine (250 mg/kg), and the left limb was placed in a lateral position and immobilized. Using the knee as a landmark, an ∼1-cm incision was made in the longitudinal direction (34). The skin was cut, muscles were bluntly dissected, and the sciatic nerve was exposed distal to its trifurcation.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were anesthetized with avertine (250 mg/kg), and the left limb was placed in a lateral position and immobilized. Using the knee as a landmark, an ∼1-cm incision was made in the longitudinal direction (34). The skin was cut, muscles were bluntly dissected, and the sciatic nerve was exposed distal to its trifurcation.…”
Section: Methodsmentioning
confidence: 99%
“…The stability of RGS9 is modulated post-translationally via its association with R7BP; binding to R7BP increases its expression, and dissociation makes it susceptible to degradation by cellular cysteine proteases decreasing the expression levels (8). Accordingly, the current model suggests that stimuli that affect RGS9 expression at the post-translational level do so by modulating the extent of its association with R7BP (66,69). Interestingly, in the case of RGS7, the primary role in regulating post-translational stability and expression levels belongs to GPR158 instead of R7BP.…”
Section: Discussionmentioning
confidence: 91%
“…We next used western blot analysis to determine if neuropathic pain modulates Rgs9-2 expression in the spinal cord and the NAc. Our earlier western blot analysis studies demonstrated Rgs9-2 immunoreactivity levels that were very abundant in the striatum with low to moderate abundances in spinal cord (Terzi, Cao, Agrimaki, Martemyanov and Zachariou 2012). This pattern of expression was also observed using in situ hybridization analysis (Zachariou et al 2003).…”
Section: Resultsmentioning
confidence: 98%